2015
DOI: 10.1049/iet-nbt.2014.0030
|View full text |Cite
|
Sign up to set email alerts
|

Drug release, cell adhesion and wound healing evaluations of electrospun carboxymethyl chitosan/polyethylene oxide nanofibres containing phenytoin sodium and vitamin C

Abstract: In this work, N, O-carboxymethyl chitosan (CMCS) samples from virgin chitosan (CS) were synthesised and CMCS/polyethylene oxide (PEO) (50/50) blend nanofibrous samples were successfully electrospun from their aqueous solution. The electrospinning conditions to achieve smooth and fine diameter nanofibrous mats were optimised via D-optimal design approach. Afterwards, vitamin C and phenytoin sodium (PHT-Na) were added to these samples for producing wound dressing materials. H-nuclear magnetic resonance, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Previously, investigators have demonstrated that the inclusion of AA in culture media can enhance keratocyte growth and endogenous collagen synthesis in glutaraldehyde crosslinked collagen‐glycosaminoglycan scaffolds . Moreover, AA released from electrospun carboxymethyl chitosan/polyethylene oxide nanofibers exhibited notable efficacy in wound closure owing to the accumulation of AA‐induced collagenous matrix and the regeneration of the epidermis layer . In accordance with these earlier findings, our results further demonstrate that by selecting a proper dendrimer generation, the resulting thermogel can possess high biocompatibility and the capability to release AA molecules at an appropriate rate, consequently enhancing collagen production in cell cultures.…”
Section: Resultssupporting
confidence: 90%
“…Previously, investigators have demonstrated that the inclusion of AA in culture media can enhance keratocyte growth and endogenous collagen synthesis in glutaraldehyde crosslinked collagen‐glycosaminoglycan scaffolds . Moreover, AA released from electrospun carboxymethyl chitosan/polyethylene oxide nanofibers exhibited notable efficacy in wound closure owing to the accumulation of AA‐induced collagenous matrix and the regeneration of the epidermis layer . In accordance with these earlier findings, our results further demonstrate that by selecting a proper dendrimer generation, the resulting thermogel can possess high biocompatibility and the capability to release AA molecules at an appropriate rate, consequently enhancing collagen production in cell cultures.…”
Section: Resultssupporting
confidence: 90%
“…14,15 The electrospinning nanofibers with very fine diameter and high porous structure have attracted increasing attention for their use in biomedical applications such as medical dressings, 16,17 tissue engineering scaffold and controlled drug delivery. 18 In this study, fish collagen was obtained from tilapia skin.…”
Section: Introductionmentioning
confidence: 99%
“…A number of natural and synthetic materials have been studied as hydrogel‐based wound dressings. With regards to this, natural biopolymers, collagen, alginate, chitosan, cellulose acetate and hyaluronic acid were explored in terms of biocompatible properties and their potential role as a wound dressing material. In this context, alginate‐based dressing material has a pharmacological function, which is because of calcium ions used as a cross‐linking agent.…”
Section: Introductionmentioning
confidence: 99%